KOMUNIKASI TERAPEUTIK PADA KLIEN REHABILITASI SOSIAL NARKOBA DI YAYASAN GENNESA BANYUWANGI: - - Ari Susanti (MEDIAKOM, 2022)
Drugs are a massive problem and difficult to eradicate. One of the government's efforts related to the handling of drug rehabilitation in Indonesia is to synergize with the community to form a Compulsory Reporting Recipient Institution that can handle medical rehabilitation and social rehabilitation for addicts and victims of drug abuse. Therefore, this study aims to determine therapeutic communication to drug rehabilitation clients at the Gennesa Banyuwangi Foundation and how the therapeutic communication strategy carried out by addiction counselors successfully handles drug rehabilitation client problems along with client handling programs carried out at the Gennesa Banyuwangi Foundation. The approach used is descriptive qualitative by conducting in-depth interviews with client informants and addiction counselors. The results of this study are (1) the social rehabilitation developed is that Gennesa is a home that is always ready to accept clients to carry out garbage disposal activities. The family climate created will facilitate smooth therapeutic communication for clients (2) the success of therapeutic communication depends on a harmonious relationship between addiction counselors and clients. The more open the client is to the addiction counselor, the faster the problem solving will be, thus accelerating the client's rehabilitation process, and (3) the programs developed in dealing with the problems of drug rehabilitation patients are inpatient, outpatient and after care with the hope that the client can go through the stages of social rehabilitation to completion. Narkoba menjadi masalah yang massif dan sulit berantas. Salah satu upaya pemerintah berkaitan dengan penanganan rehabilitasi narkoba di Indonesia adalah bersinergi dengan masyarakat membentuk Institusi Penerima Wajib Lapor yang dapat menangani rehabilitasi medis dan rehabilitasi sosial pada pecandu dan korban penyalahgunaan narkoba. Oleh karena itu, penelitian ini bertujuan untuk mengetahui komunikasi terapeutik pada klien rehabilitas narkoba di Yayasan Gennesa Banyuwangi dan bagaimanakah strategi komunikasi teraputik yang dilakukan konselor adiksi berhasil menangani masalah klien rehabilitasi narkoba beserta program penanganan klien yang dilakukan di Yayasan Gennesa Banyuwangi. Pendekatan yang digunakan adalah deskriptif kualitatif dengan melakukan wawancara mendalam kepada informan klien dan konselor adiksi yang berada di Yayasan Hasil penelitian ini adalah (1) rehabilitasi sosial yang dikembangkan adalah Gennesa adalah rumah yang selalu siap menerima klien untuk melakukan aktiivitas buang sampah. Iklim kekeluargaan yang diciptakan akan memudahkan kelancaran komunikasi terapiutik bagi klien (2) keberhasilan komunikasi terapiutik tergantung dari hubungan yang harmonis antara konselor adiksi dan klien. Semakin terbuka klien kepada konselor adiksi maka penyelesaian masalah akan semakin cepat sehingga mempercepat proses rehabilitasi pada klien, dan (3) Program-program yang dikembangkan dalam menangani masalah pasien rehabilitasi narkoba yaitu rawat inap, rawat jalan dan after care dengan harapan, klien dapat melalui tahapan rehabilitasi social hingga tuntas.